THE INFLUENCE OF GREEN MARKETING MIX ON LE MINERALE PRODUCT PURCHASE DECISIONS (case study on le minerale consumers in Subang City) - Sukmawati Sukma; Devy Widya Apriandy (JABI (Journal of Accounting and Business Issues), 2025)
Green marketing mix plays an important role in shaping consumer preferences, particularly in industries that are highly exposed to environmental issues such as bottled drinking water. This study aims to examine the influence of the green marketing mix on purchase decisions of Le Minerale consumers in Subang City, considering the growing awareness of sustainability in consumption patterns. This research employs a quantitative method with a descriptive-verificative approach. Data were collected through questionnaires distributed to 55 respondents who had purchased Le Minerale in the past month. The descriptive analysis reveals that the green marketing mix is perceived to be in the “good” category with an average score of 87%, while purchase decisions are also categorized as “good” with an average score of 85%. The results of a simple linear regression analysis indicate that the green marketing mix has a positive and significant effect on purchase decisions, with a determination coefficient of 43.8% and a t-value of 6.556 (Sig. 0.000 < 0.05). These findings highlight that the more effectively Le Minerale implements environmentally friendly product, price, place, and promotion strategies, the higher the likelihood of consumer purchase decisions.